“Criança não deveria morrer”: significados atribuídos por profissionais de saúde ao paliar crianças em iminência de morte - PAMPOLHA, Simone dos Santos Abraão (Universidade Federal do Pará, 2014)
This study aims to understand the meanings attributed by professionals working in the pediatric ward on the care of children with no possibility of curing disease, hospitalized and dying process. The strategy was based on a qualitative approach, which is a method concerned with the peculiarities and particularities of an object, without the pretense of absolute truths or generalizations about the findings. The research was conducted in the Clinical Care Pediatric University Hospital João de Barros Barreto, linked to the Federal University of Pará in Belém-Pa. Collaborated with research twelve (12) Professional, 3 doctors, one psychologist, one occupational therapist, two nurses, one physiotherapist, one social worker and 3 Nursing Technicians who deal daily with the process of dying children admitted in this institution. As an instrument for data collection was used to semi-directed, and performed the thematic content analysis, by identifying three central themes: The Denial of Death and Prohibition; Addictions and Bereavement Experience and Training remedy. To alleviate employees is an arduous task involving carefully targeted to children without curative therapeutic possibilities. However, unable to prevent the death of the child professionals can experience intense suffering, which favors obstinate actions for sustaining life, denial and interdiction of death. As parents attached and caring for their children, on the verge of death or death of the child, the typical professional experience feelings of grief. Regarding the training of health professionals highlights the absence of disciplines addressing the topic of death and dying during the years of graduation, calling attention to the need to include these in the undergraduate curriculum. The findings suggest the strangeness front of the child's death and the experience of mourning unauthorized, supporting actions in favor of education for life and death.